RELIGIUSITAS TENAGA KERJA INDONESIA DI DUA TANAH SUCI - Lukman, Dikdik Dahlan (FASTABIQ: JURNAL STUDI ISLAM, 2023)
Although only once in a lifetime, every Muslim who still has faith, must have the desire to visit the two holy lands to perform Hajj or Umrah.  Being in Mecca and Medina makes one feel close to Allah and the Prophet. It is not surprising that every pilgrim to the two holy lands is always at the peak of their religiosity. Does this apply to everyone who is in the holy land? The essence of this research is to find out the religiosity of Indonesian workers in the two holy lands.  The research conducted is qualitative through observation and interview methods related to the religiosity of Indonesian migrant workers in the midst of their busy profession (random). The data collected, classified and compiled for further processing and analysis. Analyzing data in the field using phenomenological, ethnographic and heuristic approaches because there are also efforts to reveal the history of the development of migrant workers in the holy land. The presence of a person in the holy land does not always have a strong effect on increasing one's religiosity. Psychological factors, such as personality and mental state; as well as social stratification factors related to one's profession greatly affect the religiosity of each. Keywords: Religiosity; migrant worker; the holy city